1999
DOI: 10.1046/j.1365-2044.1999.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal haematoma following epidural anaesthesia in a patient with eclampsia

Abstract: SummaryA patient with a twin pregnancy required a Caesarean section for severe pre-eclampsia. Her platelet count was 71 × 10 9 .l À1 . Epidural anaesthesia was performed after platelet transfusion. A spinal epidural haematoma was diagnosed postoperatively. A generalised tonic-clonic seizure sparing the lower limbs enabled early diagnosis to be made. The patient recovered with no permanent neurological damage after laminectomy and clot removal. The risks and benefits of regional techniques require careful consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 34 publications
0
47
0
1
Order By: Relevance
“…Three of these occurred in women with preeclampsia and thrombocytopenia. 14,15 In one report 14 the platelet count was 71 · 10 9 /L and in the other two, the platelet count was not reported. 15 Therefore, caution must be used when one is faced with the decision of placing a neuraxial anesthetic in the patient with thrombocytopenia, and a machine that evaluates platelet function would be useful.…”
Section: Discussionmentioning
confidence: 92%
“…Three of these occurred in women with preeclampsia and thrombocytopenia. 14,15 In one report 14 the platelet count was 71 · 10 9 /L and in the other two, the platelet count was not reported. 15 Therefore, caution must be used when one is faced with the decision of placing a neuraxial anesthetic in the patient with thrombocytopenia, and a machine that evaluates platelet function would be useful.…”
Section: Discussionmentioning
confidence: 92%
“…Third, most spinal epidural hematomas occurred in patients with HELLP syndrome and not preeclampsia with no evidence of HELLP syndrome (5,(21)(22)(23). Moreover, epidural anesthesia was the preferred method in those complicated cases (24,25). Vigil-De Gracia and colleagues reported 36 patients with HELLP syndrome with platelet counts below 100,000/µL who received regional anesthesia and no epidural hematoma was suffered by any of the patients (12 patients had platelet counts below 50,000/µL) (26).…”
Section: Discussionmentioning
confidence: 99%
“…Although a case report described a spinal haematoma requiring emergency laminectomy after epidural anaesthesia for caesarean section in a woman with severe preeclampsia and rapidly decreasing platelets, 23 other authors have reported uncomplicated epidural anaesthesia in pregnant women with profound thrombocytopenia. In 30 patients with platelet counts ranging between 69 and 98 · 10 9 /L, epidural anaesthesia was performed without bleeding complications.…”
Section: Coagulation Problemsmentioning
confidence: 98%